2005
DOI: 10.1007/s00040-004-0773-x
|View full text |Cite
|
Sign up to set email alerts
|

The fate of Corydalis cava elaiosomes within an ant colony of Myrmica rubra: elaiosomes are preferentially fed to larvae

Abstract: The diaspores of many plant species are adapted to dispersal by ants (myrmecochory). The ants carry the diaspores into their nests where the appendages of the diaspores (elaiosomes) are consumed. Little is known, however, about the fate of diaspores in the colony, i.e., whether elaiosomes are consumed only by the larvae or also by the workers. In this study, the distribution of Corydalis cava (Fumariaceae) elaiosomes was monitored between the larvae and the working caste of laboratory colonies of Myrmica rubra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…Indeed, benefits due to myrmecochory are far less known for ants. While more than two hundred papers tell us about plant benefits, only seven studies have shown so far that ants can benefit from elaiosomes by using them to feed their larvae (Handel, 1976;Morales and Heithaus, 1998;Bono and Heithaus, 2002;Fischer et al, 2005;Gammans et al, 2005;Marussich, 2006;Fokuhl et al, 2007) what may increase gynes production in some ant species (Morales and Heithaus, 1998) or increase larval weight (Gammans et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, benefits due to myrmecochory are far less known for ants. While more than two hundred papers tell us about plant benefits, only seven studies have shown so far that ants can benefit from elaiosomes by using them to feed their larvae (Handel, 1976;Morales and Heithaus, 1998;Bono and Heithaus, 2002;Fischer et al, 2005;Gammans et al, 2005;Marussich, 2006;Fokuhl et al, 2007) what may increase gynes production in some ant species (Morales and Heithaus, 1998) or increase larval weight (Gammans et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While quite a number of stable isotope studies have been published for tropical ants (e.g., Fisher et al, 1990;Sagers et al, 2000;Fischer et al, 2002;Blüthgen et al, 2003;Davidson et al, 2003;Tillberg and Breed, 2004;Blüthgen et al, 2006), there is a surprising paucity of such investigations in the temperate zones (but see Fischer et al, 2005;Mooney and Tillberg, 2005;Platner, 2006;Tillberg et al, 2006). Moreover, based on in-depth analysis of intracolonial and intraspecific variation of N and C isotopes in temperate-zone ants, notes of caution have recently been sounded regarding the interpretation of stable isotope data in social insects in general (Tillberg et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This appendage elicits ants to transport the elaiosomebearing diaspores back to their nest. After it has been consumed mostly by the larvae (Fischer et al, 2005), the ants discard the intact seed with other food remains. By transporting the vulnerable seeds soon after their release, ants allow plants to colonize new habitats (Gorb and Gorb, 2003), reduce intraspecific competition and decrease mortality by predation and fire (Heithaus, 1981;Bond and Slingsby, 1984;Hughes and Westoby, 1992;Boulay et al, 2007aBoulay et al, , 2009a.…”
Section: Introductionmentioning
confidence: 99%